Translation Analysis of Politeness Strategies in Directive Speech Acts in The Amazing World of Gumball Season 2 - Ainsinqof, Nun Dhiya (Universitas Sebelas Maret, 2000)
This study analyzes politeness strategies in directive speech acts performed by the main characters in The Amazing World of Gumball Season 2. Using a qualitative descriptive approach, the data consist of directive utterances from two main characters, supported by document analysis and informant input. The research is grounded in Brown and Levinson’s (1987) politeness theory, Searle’s (1979) classification of directives, Molina and Albir’s (2002) translation techniques, and Nababan et al.’s (2012) model of translation quality assessment. The findings reveal three types of politeness strategies: bald on record (46.23%), positive politeness (30.19%), and negative politeness (23.58%), with no instances of off-record strategies. Thirteen shifts in politeness strategies were identified due to translation techniques, with reduction being the most influential. Despite these shifts, the overall translation quality remained accurate and acceptable, aligning with the cartoon’s humorous and friendly tone.